Urinary PYD/Creatinine Ratio Has Negative Correlation to Serum 25(OH)D and Positive Correlation to Chronic Lead Exposure Index - Hajar, Siti Sarah; Mudjihartini, Ninik; Manikam, Nurul Ratna Mutu; Mulyana, Mulyana; Mansyur, Muchtaruddin (The Prodia Education and Research Institute (PERI), 2024)
BACKGROUND: The burden of disease due to lead exposure continues to increase. Lead interferes with 25(OH)D hydroxylation and calcium transport, increasing osteoclastic activity and bone resorption. Pyridinoline crosslinks (PYD), as an indicator of bone damage, can be seen earlier compared to imaging changes. Therefore, it is necessary to determine the correlation between serum 25(OH)D levels and the urinary PYD/creatinine ratio in workers exposed to lead, since up to now, there are only limited studies related to it.METHODS: This cross-sectional study involved 104 workers exposed to lead, selected from parents whose children had blood lead levels above 10 µg/dL. Questionnaires and physical examination were performed to obtain characteristic data from subjects. Data regarding blood lead levels, serum 25(OH)D levels, urinary PYD levels, and urinary creatinine levels were also obtained from various laboratory methods.RESULTS: Most subjects (86.5%) had inadequate serum 25(OH)D. Median blood lead levels was 6.3 (1.2-35.5) µg/dL, chronic lead exposure index was 35.3 (1.2-535.8) years µg/dL, serum 25(OH)D levels was 22 (8-52) ng/mL, and urinary PYD/creatinine ratio was 5.3 (3.6-28.1)×10-6. There was a significant negative correlation between serum 25(OH)D levels and urinary PYD/creatinine ratio in workers exposed to lead. There was also a significant positive correlation between chronic lead exposure index and the urinary PYD/creatinine ratio.CONCLUSION: Since urinary PYD/creatinine ratio is correlated with serum chronic lead exposure index and serum 25(OH)D levels, it suggests that pyridinoline might be a potential biomarker to detect bone metabolism disorder due to the chronic lead exposure. Vitamin D adequacy is also an important factor in preventing bone metabolism disorder amidst chronic lead exposure.KEYWORDS: 25(OH)D, bone resorption, pyridinoline, lead, worker